Fenomena Doomscrolling terhadap Informasi Oversharing di Media Sosial pada Mahasiswa Program Studi Perpustakaan dan Ilmu Informasi Universitas Negeri Padang - Faunesya, Faunesya; Ardoni, Ardoni (Scinary, 2025)
The purpose of this study is to describe the phenomenon of doomscrolling regarding oversharing information on social media among students in the Library and Information Science Program. This research uses a qualitative method with a phenomenological approach and employs snowball sampling to determine the informants. Data collection is conducted through observation, interviews, and documentation. The data analysis involves five stages: (1) reading and re-reading, (2) initial analysis, (3) developing emerging themes, (4) finding relationships between themes, and (5) analyzing emerging patterns. The results indicate that students in the Library and Information Science Program spend an average of 3-5 hours per day doomscrolling on social media platforms such as TikTok, Twitter, and Instagram, with the accessed information being predominantly emotional and personal. The motives for students engaging in doomscrolling of oversharing information are: (1) entertainment motives, (2) informational motives, (3) social motives, and (4) desire-driven motives. The impacts of doomscrolling on oversharing information are: (1) psychological effects, (2) time and concentration on studying, and (3) information evaluation and dissemination.